Linguistic Culture Expressing Happiness and Contentment in The English And Uzbek Languages - Ilhomjonovna, Ozoda Jumayeva; Ikromovich, Izzatulla Akromov; Ramazonovna, Mohigul Saparova (International Journal of Psychosocial Rehabilitation, 2020)
The interest in happiness, its material attributes and intangible components in different cultures within the framework of various areas of humanitarian anthropological knowledge is evidence that feelings associated with happiness, its attributes characterize the spiritual essence of man. The relevance of the topic of our study is determined by the fact that understanding of happiness reflects the value needs of a person in different cultures, thereby allowing researchers to draw conclusions about the origins of culture, which is the foundation for the formation of the ethnic, collective, national consciousness of its carriers. Attitude to happiness allows revealing the existential characteristics, norms, traditions of different social groups, since a different interpretation of happiness within the framework of different cultures reveals their ethno cultural specificity and perception of the world and people.